Controversies and Common Ground in Wild and Domestic Fine Fiber Production in Argentina - Von Thungen, Julieta; Martin, Elisa; Lanari, Maria Rosa (Frontiers Media, 2021)
This work analyzes possible obstacles to developing new products or old merchandise using an innovative method. It will look into stakeholders of fine fiber and meat products from three distinctive socioecological systems. Through three case studies, we explore how natural resources management is connected to interests, values, and knowledge by stakeholders, which include government, the scientific community, and people with rural livelihoods. The government vertex is the national and provincial authorities involved with decision-makers at the national and provincial level. The Scientific-Technological vertex includes researchers from INTA, CONICET, and Universities. Rural livelihoods include livestock keepers, farmers, and local people with traditional knowledge. We will address the goods and services provided by two species of wild camelids and domestic livestock. The three cases have both similarities and differences in their focus and common ground of controversial spaces. They create complex networks of relationships and bonds leading to diverse outcomes. Top-down or bottom-up experiences hold distinct epistemology and research consequences, they affect rural livelihoods in various ways. For the three rural livelihoods, meaningful regulations should be endogenous social constructions. However, there are no longitudinal studies on the trajectories of these case studies. Long-term multispecies grazing opportunities are available for the three case studies. It depends on how stakeholders identify flexibility in their common ground to enable resilience to catastrophic events.